2017
DOI: 10.1093/jme/tjx106
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia Species Detected in Ticks Feeding on Wild Korean Water Deer (Hydropotes inermis) Using Molecular and Genotypic Analyses

Abstract: Lyme borreliosis is a vector-borne disease transmitted through the bite of ticks infected by Borrelia burgdorferi sensu lato group, including B. burgdorferi sensu stricto, B. afzelii, and B. garinii. The goal of the present study was to detect Borrelia species in ticks infesting wild Korean water deer (KWD; Hydropotes inermis Swinhoe), using molecular and genotypic analyses. In total, 48 ticks were collected from KWD, all of which were morphologically identified as Haemaphysalis longicornis Neumann that is dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Consistently, Borrelia spp. have been identified in Ixodes and Haemaphysalis ticks in Korea and Japan [40,41]. Pal et al [23] revealed that tick receptor for ospA (TROSPA) acts as a receptor for Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistently, Borrelia spp. have been identified in Ixodes and Haemaphysalis ticks in Korea and Japan [40,41]. Pal et al [23] revealed that tick receptor for ospA (TROSPA) acts as a receptor for Borrelia spp.…”
Section: Discussionmentioning
confidence: 99%
“…owing to its conserved characteristics among Borrelia spp. [31,40,43]. However, as suggested by De Michelis et al [6], it is difficult to construct a reliable molecular phylogeny based on only rrf-rrl owing to the fact that the fragment is short and consists of highly conserved and variable regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…was amplified by PCR using the genus-specific primer set Rr17.61p/Rr17.492n with the following program: pre-denaturation at 94°C for 3 min; 35 cycles of denaturation at 94°C for 30 sec, annealing at 55°C for 45 sec and extension at 72°C for 1 min; and a final post-extension step at 72°C for 7 min [ 24 ]. The 5S ( rrf )–23S ( rrl ) intergenic spacer gene of Borrelia was amplified by nested PCR (nPCR) using two primer sets, Bb23S3/Bb23Sa and Bb23SnF/Bb23SanR with the following program: pre-denaturation at 96°C for 2 min; 30 cycles of denaturation at 94°C for 30 sec, annealing at 55°C for 30 sec and extension at 72°C for 40 sec; and a final post-extension step at 72°C for 5 min, and the outer surface protein A gene fragment of B. burgdorferi was amplified by nPCR using two primer sets, N1/C1c and N2/C2c with the following program: pre-denaturation at 95°C for 3 min; 20 cycles of denaturation at 95°C for 30 sec, annealing at 40°C for 1 min and extension at 72°C for 1 min, which was then followed by 40 cycles of denaturation at 95°C for 30 sec, annealing at 50°C for 1 min and extension at 72°C for 1 min; and a final post-extension step at 72°C for 7 min [ 32 ]. Multiple primer sets were used to amplify the 16S rRNA of the genus Coxiella , including C. burnetii and Coxiella -like bacteria with the following program: pre-denaturation at 93°C for 3 min; 30 cycles of denaturation at 93°C for 30 sec, annealing at 56°C for 30 sec and extension at 72°C for 1 min; and a final post-extension step at 72°C for 5 min [ 26 ].…”
mentioning
confidence: 99%